The Psychometric Properties of the Norwegian version of Children’s Global Assessment Scale (CGAS) - Jozefiak, Thomas; Hanssen-Bauer, Ketil; Bjelland, Ingvar (PsykTestBarn, 2018)
Description: Psychometric properties of the Norwegian version of Children's Global Assessment Scale (CGAS). PsykTestBarn, 1:3. Description. The Children’s Global Assessment Scale (CGAS) was developed by David Shaffer and colleagues at Columbia University, in 1983. The CGAS was adapted from the Global Assessment Scale for adults (GAS) and is scored by clinicians as a measure of a child’s or adolescent’s psychosocial functioning during the month before assessment, on a scale from 1 (lowest functioning) to 100 (superior functioning in all areas). It is recommended for children and adolescents aged 4 to 16/17 years. The CGAS is scored by clinicians and takes less than 10 minutes to complete. It is unknown whether there are competence requirements to score the instrument. New information on translation and copyright in 2022. There is now an officially approved Norwegian translation of CGAS from the copyright holders at Columbia University, USA. It was translated in August 2022 by Lars Ravn Øhlckers, Børge Idar Mathiassen and Ketil Hanssen-Bauer, on behalf of the University Hospital of Northern Norway and is free for non-profit use both digitally and in paper format. Literature search: We included 34 Norwegian articles, of which 19 had more than 100 participants. Most of the participants were children and adolescents aged 6-18 years, but a few follow-up studies into adulthood were also included. The included studies varied considerably with regard to clinical samples, and there were both cross-sectional and longitudinal studies. Psychometrics: We found satisfactory evidence for convergent, discriminant, and predictive validity and interrater reliability, somewhat less for sensitivity to change. There was a lack of test-retest reliability studies. Conclusion. Conclusion: We recommend the use of the Norwegian version both in research and clinical practice, provided that clinicians receive adequate training in scoring.